Judicial Scrutiny of Indonesian Migrant Worker Placement Under the Guise of Training - Fabrian Candra Darmawan; Hafid Zakariya; Suparwi Suparwi (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The widespread placement of Indonesian Migrant Workers (Pekerja Migran Indonesia [PMI]) through unauthorized Job Training Institutions (Lembaga Pelatihan Kerja [LPK]) reflects continuing weaknesses in the oversight of non-procedural labor migration, increasing the risk of exploitation, human trafficking, and human rights violations. This study analyzes the judicial application of law in assessing the constituent elements of the criminal offense of migrant worker placement through unlicensed LPKs, as reflected in Boyolali District Court Decision Number 158/Pid.Sus/2023/PN Byl, while evaluating the effectiveness of judicial reasoning in protecting victims. Using a normative legal method with statutory, case-based, and conceptual approaches, the study finds that the panel of judges appropriately distinguished the authority of LPKs and Perusahaan Penempatan Pekerja Migran Indonesia (P3MI) based on SIP2MI ownership and affirmed the defendant’s criminal liability. However, victim restoration mechanisms remain inadequate, particularly regarding restitution and rehabilitation.